Citra Starbucks Pasca Kasus Pemboikotan Pro Israel - Alya Zalfa Haniyah; Annisa Meliani Dewi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Starbucks is a coffee processing company that has very fast sales and is very popular among consumers. Therefore, many branches are spread throughout the world. Images represent how others view your company, employees, committees or activities. Every company has as much image as people see it. A PR crisis is an event, rumor or information that negatively impacts a company's reputation, image or credibility. This research uses a qualitative approach to explore deeper information regarding the role of public relations in restoring the image of public companies